THE AUTHORITY OF THE VILLAGE CONSULTATIVE BODY (BPD) IN PREPARING THE VILLAGE REVENUE AND EXPENDITURE BUDGET (APBDES) IN GUMELAR VILLAGE, GUMELAR DISTRICT, BANYUMAS REGENCY IN 2020 - Elsa Ayu Putu Sarga (Ganesha Law Review, 2021)
Based on the results of research and discussion, it can be concluded that the authority of the Village Consultative Body (BPD) in the preparation of the 2020 Village Revenue and Expenditure Budget (APBDes) in Gumelar Village, Gumelar District, Banyumas Regency is regulated in Article 12 letter a of the Banyumas Regency Regional Regulation Number 11 of 2015 About the Village Consultative Body. This authority is exercised by the BPD by discussing the draft village regulation on APBDes as outlined in the Memorandum of Understanding between the Gumelar Village Government and the Gumelar Village Consultative Body Number: 142/1/2020 dated: January 8, 2020 concerning Joint Agreement on the Draft Gumelar Village Regulation Regarding the Budget and Revenue. Gumelar Village Expenditure, Gumelar Subdistrict, Banyumas Regency, Fiscal Year 2020, Becomes a Village Regulation.